Are banks profitable and efficient? A case of Pakistan - Muhammad, Ali; Chin Hong, Puah (Inderscience Enterprises Ltd., 2022)
The aim of this study is to investigate the impact of bank-specific factors and macroeconomic environment on bank profitability and management efficiency in Pakistan. The sample data comprised of 24 banks over a sample period of 2007-2015. The panel least squares regression with fixed effect model suggests that bank profitability is significantly affected by bank size, credit risk and bank stability. On the other side, bank efficiency was significantly predicted by liquidity risk, credit risk and funding risk. The robustness of results was also confirmed in the presence of the macroeconomic environment. Overall, this research provides a new insight into bank profitability and efficiency literature. Additionally, prior studies have neglected the management efficiency as the dependent variable. Therefore, we consider this article as superior, which has laid a foundation for future studies.